2020
DOI: 10.1088/1741-4326/ab71bb
|View full text |Cite
|
Sign up to set email alerts
|

Tensile stress-driven cracking of W fuzz over W crystal under fusion-relevant He ion irradiations

Abstract: Although W fuzz is formed in the divertor region of the fusion reactor, no theory may clearly explain the W fuzz growth mechanism. In this study, we observe the growth process of W fuzz over W crystal under ITER-relevant He ion irradiations. We propose the tensile stress-driven cracking of nano-structured fuzz during the initial growth of W fuzz. We demonstrate that the existence of tensile stress is due to the swelling of He nano-bubbles in the fuzz. After this cracking, the W fuzz breaks away from the planar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…9,10 The indicated aspects, related to the stability of the fuzzy surface layers, then provide motivation for a deeper investigation into the structural attributes, and mechanical characteristics, of such morphologies. 11 Given the intrinsic fragility as well as the nanometer length scales, the mechanical properties of the fuzzy layer may be best monitored through nanoindentation-based measurements. While a previous study indicated fuzz deformation, there was little quantification of the related mechanical attributes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The indicated aspects, related to the stability of the fuzzy surface layers, then provide motivation for a deeper investigation into the structural attributes, and mechanical characteristics, of such morphologies. 11 Given the intrinsic fragility as well as the nanometer length scales, the mechanical properties of the fuzzy layer may be best monitored through nanoindentation-based measurements. While a previous study indicated fuzz deformation, there was little quantification of the related mechanical attributes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to nuclear engineering-related applications, the refractory characteristics of W are also utilized for a cost-effective and sustainable material in high current density cathodes, , where the stability of the electric field-induced roughness and surface layers is of much importance. Furthermore, it has been suggested that fuzzy W-based morphologies have a large surface area-to-volume ratio and may be used in various applications, ranging from energy generation to gas sensing. , The indicated aspects, related to the stability of the fuzzy surface layers, then provide motivation for a deeper investigation into the structural attributes, and mechanical characteristics, of such morphologies …”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) images have shown that in addition to the large bubbles that rupture, there are many small bubbles within the bulk and the individual tendrils [14]. The stresses within the large bubbles, and from the surrounding smaller bubbles, likely drive bubble rupture [20].…”
Section: Bubble Growth and Rupturementioning
confidence: 99%
“…In some models, it is proposed that the He bubbles reach pressures that exceed the yield strength of W, inducing dislocation loop-punching in the bulk or causing bubbles at the surface to rupture, leaving thin pieces of the bubble shell behind as nucleation sites for the process to continue. [14][15][16][17] In other models, He bubbles with pressures marginally below that needed to overcome the yield strength of W could lower the viscosity of the W on the surface and allow viscoelastic flow along the surface to deformities and nano-tendril tips. 18 Finally, there is the possibility that the He bubbles are a source of tensile stress in the surface, which lowers the chemical potential over the surface of bubbles, causing a net flux of adatoms generated by the He ion bombardment toward the bubble apexes, where the adatoms may become trapped and form the tendrils.…”
Section: Introductionmentioning
confidence: 99%